"\\text{1. Given \\( z = ax + by\\) then we will have the following: } \\\\\n\\displaystyle \\frac{\\partial z}{\\partial x} = a \\text{ and } \\displaystyle \\frac{\\partial z}{\\partial y} = b\\\\\n\\text{Inserting these into \\(z = ax + by\\) we have}\\\\\n\\displaystyle z = x\\frac{\\partial z}{\\partial x} +y\\frac{\\partial z}{\\partial y} \\\\\n\\text{which is equivalent to: } \\\\\nx\\frac{\\partial z}{\\partial x} +y\\frac{\\partial z}{\\partial y} - z = 0 \\\\\n\\text{2. Given \\( z = ax \\) then we will have the following: } \\\\\n\\displaystyle \\frac{\\partial z}{\\partial x} = a \\\\\n\\text{Inserting these into \\(z = ax\\) we have}\\\\\n\\displaystyle z = x\\frac{\\partial z}{\\partial x}"
Comments
Leave a comment